Softwares de análise acústica como ferramenta pedagógica no ensino do canto - Greyce Ornelas Viana Teixeira (2017)
This present work presents an exploratory research whose objective is to investigate how acoustic analysis softwares can act as pedagogical tool in lyric singing lessons in a Brazilian institution of higher education. The research used an exploratory methodology, in controlled environment, that is, in a laboratory. Seven sopranos and a singing teacher used the acoustic analysis software in two vocalizes to visualize three vocal technical aspects: (1) vocal quality; (2) regularity of the vibrato, and (3) breaking in the vocal registers. Each of these excerpts was sung and investigated in three different situations: (1) without visual feedback and without the guidance of the teacher; (2) with visual feedback, but without teacher's guidance; (3) with visual feedback and teacher guidance. The results point to improvements in the performance of the singers with visual feedback, mainly with the help of the teacher. The most experienced sopranos obtained better results with the use of the software, which was confirmed by the literature. The knowledge about acoustic and physiology of the voice is essential in the use of this kind of tool, which has proved to be very useful in visualizing and improving the vocal technical aspects worked.